Partisipasi Masyarakat dalam Restorasi Gambutdi Desa Rimbo Panjang - Syafrizal Syafrizal; Resdati Resdati (Mahesa Research Center, 2020)
This study aims to determine how community participation in peatland restoration activities in Rimbo Panjang village. The research method uses primary and secondary data sources. Primary data is obtained through interviews with the village community of Rimbo Panjang while secondary data is data obtained by researchers from indirect data sources by collecting information and references related to the problem under study. The research sample took figures deemed necessary in the research, namely village officials, fire fighting community groups, sustainable peat community groups, noble peatland community groups and thorn pineapple community groups. The method used is verstehen or also known as interpretive understanding, which is a way or an attempt to understand an act of subjective meaning / meaning for oneself and associated with others. The results of this study indicate that community participation in peat restoration, village officials and community groups as well as with BRG-Kemitraan. Restoration in this case is known as 3R, namely Rewetting, Revegetation or replanting and revitalization or improvement of community welfare. Benefits that are felt by the community, such as wetting, are drilling wells, providing tools and patrolling, in the field of community empowerment through training in catfish businesses, prickly pineapple community groups and agriculture by providing seeds, fertilizers to peatland farmers.